Principal Instructional Leadership for Digital Literacy Culture in Two Siak Junior High Schools - Marlinda Rosa; Meilina Bustari (Journal of Education and Teaching Learning, 2026)
This study examined the role of principal instructional leadership in developing a digital literacy culture at SMP Negeri 2 Siak and SMP Negeri 3 Siak. It focused on strategies used to address barriers and optimize digital literacy implementation. Using a qualitative approach, data were collected through interviews, observation, and documentation. The findings show that principals play strategic roles in defining school missions, managing instructional programs, and creating a climate conducive to digital literacy development. Key strategies include teacher training, the provision of technology facilities, and efforts to secure external support for digital infrastructure. The study also identifies continuing challenges, particularly uneven teacher digital competence, limited funding, and unequal student access to technology. These findings underscore the importance of proactive, technology-oriented instructional leadership in integrating digital literacy into school learning and management. The study offers policy recommendations and practical considerations for building a sustainable digital literacy culture in schools.